Seismicity, tectonics and oil-and-gas bearing of the crust of Bukovyna in the RP-5 profile zone - Nazarevych, L.Ye.; Sheremeta, P.M.; Nazarevych, A.V. (Geofizicheskiy Zhurnal, 2025)
The work analyzes the seismicity and oil and gas potential of Bukovyna in connection with the crust’s deep structure. The crust’s deep structure was analysed using published and archival data. These included data on the regional profile RP-5, data in the areas of oil and gas fields and in the area of the Dniester hydroelectric complex. Noticeable seismic activity of the diagonal faults of the Carpathian extension was established both under the Carpathian thrusts and in the area of the Dniester hydrocascade. Orthogonal fault structures were also found to be active. The oil and gas potential of the territory is largely associated with the Subcarpathian folds of the autochthon (Mesozoic) in the subthrust of the Carpathians, this is clearly seen in the example of the Lopushna oil field. The extension of the Trans-European ancient rift Teisseire-Tornquist Zone has also been traced here between the Selyatyn faults in the southwest and the Forecarpathian faults in the northeast. Also of interest are the band of intrusions in the basement under the foreland of the Carpathians and the northeast-dipping «contact» zone of probably Hercynian age between the structures of the Forecarpathian Trough and the edge of the consolidated East European platform in the southwestern outskirts of Volyn-Podillia.